КАРТОГРАФИЧЕСКИЙ МЕТОД ИССЛЕДОВАНИЯ ОВРАЖНОЙ ЭРОЗИИ - Никольская И.И.; Прохорова С.Д. (My University, 2005)
Authors consider the geographic map as the main source of information about gully erosion. Special maps of erosion factors make it possible to show the different aspects of the distribution and the development of gully formation. They in-volve quantitative characteristics of gully density, area affected and intensity of the process. The latter may be represented as gully runoff module on the catch basin of the larger links of drainage network.
Keywords: 551.4.012:551.435.162(470.1/.6)